Surface modification PVA hydrogel with zwitterionic via PET‐RAFT to improve the antifouling property. Issue 24 (6th March 2019) - Zhou, Jinsheng; Ye, Lin; Lin, Yanming; Wang, Ling; Zhou, Li; Hu, Huiyuan; Zhang, Qilong; Yang, Hui; Luo, Zhongkuan
ABSTRACT: To improve the antifouling property, polyvinyl alcohol hydrogel was successfully grafted with [2‐(methacryloyloxy) ethyl] dimethyl‐(3‐sulfopropyl) ammonium hydroxide (MEDSAH) via photoinduced electron transfer–reversible addition–fragmentation chain transfer (PET‐RAFT) polymerization under a 10 W blue (450–460 nm) light‐emitting diodes. It is surprising that the reaction could be performed in the presence of oxygen, which meant that the reaction has a great prospect of industrialization. The highest grafting percentage (GP) was 55.77% by adding triethylamine and changed the MEDSAH usage in the absence of oxygen. Thermal gravimetric analysis exhibited that grafted MEDSAH affects the thermal property of PVA hydrogel. Also, there was no influence on the ultraviolet–visible transmittance, and the PVA‐g‐pMEDSAH hydrogel became hydrophilicity after grafting. Moreover, in vitro cytotoxicity of both PVA and PVA‐g‐pMEDSAH hydrogel was noncytotoxic according to ISO 10993‐2009. The antifouling property of PVA‐g‐pMEDSAH hydrogel was increased about 53.05%. Thus, the PVA‐g‐pMEDSAH hydrogel can be an ideal optical biomaterial candidate. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47653. Abstract :